Taphonomic signatures in concentrations of Heleobia Stimpson, 1865 from Holocene deposits of the Salado river basin, Buenos Aires, Argentina: their utility in paleoenvironmental reconstructions - Pisano, Florencia (2015)
Assemblages composed ofHeleobia parchappiiandH. australisconstitute the dominant elements in Quaternary deposits of the Pampean Region in the province of Buenos Aires. This study describes and analyzes the degree of preservation of shells of both species recovered from nine Holocene localities in order to describe and quantify taphonomic alterations, evaluate if preservation varied during the Holocene, and assess their utility as paleoenvironmental bioindicators.Heleobia parchappiidisplayed better overall preservation thanH. australis, with little evidence of fragmentation, limited principally to levels with highest densities. On a temporal scale, no significant differences in fragmentation were found, whereas corrasion and luster displayed temporal differences.